Dispersal of Syzygium cormiflorum (F. Muell.) B. Hyland. around the main trees in Lamedae Natural Reserve, Kolaka, Southeast Sulawesi - DEDEN MUDIANA (Biodiversitas Journal of Biological Diversity, 2005)
This research was sampled 52 main trees in the Lamedae Natural Reserve. Seedling and sapling of Syzygium cormiflorum (F. Muell.) B. Hyland. dispersed far away from the main trees. Only 6,308 seedlings per trees and 0,903 saplings per trees was founded growth around the main trees. The seed dispersal of S. cormiflorum was done by wild animals such as birds, mammals, etc. Analysis of the data showed that higher of main trees more have corelation with sum of seedling or sapling was compared with diameter of main trees.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: dispersal, Syzygium cormiflorum, seedling, sapling, main trees, Lamedae natural reserve.